2022
DOI: 10.1111/jnu.12866
|View full text |Cite
|
Sign up to set email alerts
|

The role of children's hospices in perinatal palliative care and advance care planning: The results of a national British survey

Abstract: Introduction Perinatal palliative care services are increasingly available globally, offering a range of clinical and psychological support services to families during pregnancy, in the neonatal period and following the death of a baby with a life‐limiting or life‐threatening condition. Little is understood about the role of children's hospice care and how it contributes to effective perinatal palliative care. Design The study aims to answer the question “what is the role of children's hospices in the provisio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 88 publications
0
5
0
Order By: Relevance
“… 57 Such an approach leads to an understanding of the biopsychosocial needs of the family and supporting parental involvement in informed decision-making. 58 , 59 Despite professional apprehensions to the contrary, parents do not view advance care planning as a means only to discuss withholding treatment or resuscitation decisions. 60 The use of advance care plans has been linked to better bereavement outcomes, and less complicated grief.…”
Section: Discussionmentioning
confidence: 99%
“… 57 Such an approach leads to an understanding of the biopsychosocial needs of the family and supporting parental involvement in informed decision-making. 58 , 59 Despite professional apprehensions to the contrary, parents do not view advance care planning as a means only to discuss withholding treatment or resuscitation decisions. 60 The use of advance care plans has been linked to better bereavement outcomes, and less complicated grief.…”
Section: Discussionmentioning
confidence: 99%
“…Roleplay in SBS enhances the experience of learners further; incorporating actors as family members in SBS scenarios can aid the sense of fidelity3 and provide nurses with the opportunity to practice projecting empathy and compassion essential elements of perinatal palliative care, recognised by both parents1 and healthcare professionals 5…”
Section: Commentarymentioning
confidence: 99%
“…A more recent survey of UK children’s hospices ( n = 30) found that the majority did not collect specific data on the number of perinatal referrals, but for the 12 services that did, the majority had seen an increase in referrals over the last 5 years. 83 Although this suggests that referrals to hospices are increasing, the small sample size makes it difficult to extrapolate the findings and it is possible that families may still be missing out on the holistic palliative care services that hospices can provide.…”
Section: Key Areas For Further Researchmentioning
confidence: 99%